A special TEM Li-ion battery sample preparation and application technique for investigating the nano structural properties of the SEI in lithium ion batteries. (2020) - Song, Xiangyun; Fu, Yanbao; Song, Chengyu; Ross, Philip; Battaglia, Vince
Abstract: Herein we describe a technique for preparing samples from cycled Li-ion batteries with minimal contact with atmospheric water for examination by TEM and to provide the results of an analysis of the SEI in Li-ion cells. The electrode samples were prepared in a glove box by manipulation with a diamond tipped pen to carefully dislodge particles directly onto the TEM sample holder. Electrodes were extracted from Li-ion cells that contained a cathode of high capacity, manganese rich NCM (HCMR-NCM). Nanometer-sized MnF2 crystal particles embed themselves in the SEI layer of the anodes as observed and confirmed by HRTEM lattice image analysis and EELS. Cross-sections of the SEI layer reveal that the thickness of the SEI and propensity for MnF2 crystal deposition is non-uniform.